Agricultural vulnerability and adaptation strategies by farmers to climate change in south-western coastal Bangladesh - Ashrafuzzaman, Md. (2022)
Agriculture in the south-western coastal region in Bangladesh (SWCRB) has high vulnerability to climate change (CC) owing to its proximity to the rivers and the coast, frequent natural disasters, and sea level rise (SLR) causing intrusion of saline water into agricultural fields. Climate change and SLR have caused an increase in soil salinity in the SWCRB over the years, exerting significant pressure on farming, traditional agriculture and means of living. This study examines the impacts of SLR and climate change on the agricultural land of Shyamnagar Upazila in Satkhira District of the SWCRB. This conceptual framework integrates socio-economic and geophysical factors to understand the vulnerability of farmers to climate change. A mixed-methods approach is used in this study with data analysis (qualitative and quantitative), including close-ended questionnaires, interviews, surveys, focus groups with regional farmers. The survey was conducted among 320 households in Shyamnager Upazila in Satkhira District of Bangladesh to identify current adaptation measures adopted by farmers considering the effects of climate change and associated impacts. Land use change analysis from 1989 to 2019 demonstrated the expansion of water coverage in the region. The study analysed secondary rainfall data available from the Bangladesh Water Development Board (BWDB) from 1968 to 2018, showing the changes in the rainfall pattern. Multiple logistic regression (MLR) analysis was employed to understand the interrelationship between adaptive measures used by farmers. It was determined that age, gender, and total income of survey respondents affected the chosen adaptation measures.